The Role of Lipid-Lowering Treatment in the Secondary Prevention of Ischemic Stroke - Alexandra Tsankof; Konstantinos Tziomalos (Diseases, 2021)
Dyslipidemia is a major modifiable risk factor for ischemic stroke. Treatment with statins reduces the incidence of recurrent ischemic stroke and also reduces coronary events in patients with a history of ischemic stroke. Therefore, statins represent an important component of secondary prevention of ischemic stroke. In patients who do not achieve low-density lipoprotein cholesterol (LDL-C) targets despite treatment with the maximal tolerated dose of a potent statin, ezetimibe should be added to their lipid-lowering treatment and also appears to reduce the risk of cardiovascular events. Selected patients who do not achieve LDL-C targets despite statin/ezetimibe combination are candidates for receiving proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors. Finally, it appears that adding icosapent ethyl might also reduce cardiovascular morbidity in patients who have achieved LDL-C targets but have persistently elevated triglyceride levels.